(Electrocatalytic Hydrogenation of Methyl Oleate and Methyl Linoleate by Titanium covered with by /Ni/SnO(x) type Systems.) - Salinas, A. S.; Gutiérrez, J. V.; Larmat G., F. E.; Ramírez-Sanabria, A. E. (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents the Electrocatalytic Hydrogenation (ECH) of methyl oleate and methyl linoleate results electrolysis potential by which active hydrogen is producedby cyclic voltametry, was established at -600 mV. The electrocatalysts used were based on Titaniumcovered with nickel systems supported over tin oxide (II) and (IV) showed dierent behavior towards the diverse substrata studied. Tin oxide (II) system was most active towards the methyl oleate hydrogenation, whereas, tin oxide (IV) system was most active to methyl linoleate hydrogenation.